Igudesman & Joo - Colorado State University, producers (managers); Lincoln Center (Fort Collins, Colo.), producers (managers) (Colorado State University. Libraries, 2016)
Date on poster is incorrect, 2/25/15 should be 2/25/16.
Classical convergence
Keywords: Igudesman & Joo (Lincoln Center, 2016)